Handbook for concrete and cement, a handbook of test methods and inspection procedures for concrete and Portland cement. - United States. Central Concrete Laboratory, Mount Vernon, N.Y. (Mount Vernon, N.Y., 1942)
At head of title: War Dept. Corps of Engineers, U. S. Army. North Atlantic Division. Central Concrete Laboratory . Mount Vernon, New York. Mode of access: Internet.